Krait bite: A Diagnostic Dilemma - Acharya, Devendra; Yadav, Preeti; B.K., Shyam Kumar; Ghimire, Prasanna; Pandey, Parash (Journal of Nepalgunj Medical College, 2024)
In Nepal, fatalities resulting from snakebites are alarmingly common, yet the issue remains inadequately addressed, prompting experts to characterize it as an imminent but overlooked crisis. Among the venomous snakes, the Common Krait stands out for its exceptionally lethal venom, rich in neurotoxins that induce muscle paralysis. Particularly in rural areas, snakebites pose a significant threat to public health. However, the diagnostic challenge posed by patients with obscure medical histories devoid of known snakebite incidents is seldom documented in medical literature. In this context, we present the case of a 22-year-old male patient presenting with nonspecific symptoms and an indistinct medical background.